Ból głowy wśród personelu medycznego = Headache among medical Staff - Kozak-Putowska, Dorota; Iłżecka, Joanna; Piskorz, Jolanta; Pietraszek, Agata (Journal of Education, Health and Sport, 2016)
Kozak-Putowska Dorota, Iłżecka Joanna, Piskorz Jolanta, Pietraszek Agata. Ból głowy wśród personelu medycznego = Headache among medical Staff. Journal of Education, Health and Sport. 2016;6(6):23-30. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.54325 http://ojs.ukw.edu.pl/index.php/johs/article/view/3536 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. Ból głowy wśród personelu medycznego Headache among medical staff Dorota Kozak-Putowska¹, Joanna Iłżecka¹, Jolanta Piskorz², Agata Pietraszek³ 1. Samodzielna Pracownia Rehabilitacji Neurologicznej, Katedra Rehabilitacji, Fizjoterapii i Balneoterapii, Uniwersytet Medyczny w Lublinie, Polska 2. Oddział Anestezjologii i Intensywnej Terapii, Wojewódzki Szpital im Zofii z Zamoyskich Tarnowskiej w Tarnobrzegu, Polska 3. Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie, Polska Adres do korespondencji: Prof. dr hab. med. Joanna Iłżecka Samodzielna Pracownia Rehabilitacji Neurologicznej UM w Lublinie 20-081 Lublin ul. S. Staszica 4/6 tel. 505569275 e-mail: joanna.ilzecka@umlub.pl Abstrakt Wprowadzenie. Ból głowy jest powszechną dolegliwością mogącą wynikać z procesu chorobowego toczącego się w organizmie, jak też być skutkiem negatywnych zachowań zdrowotnych, nieprawidłowego stylu życia lub szkodliwych warunków pracy. Cel pracy. Analiza częstości i przyczyn występowania bólu głowy wśród personelu medycznego i jego wpływ na funkcjonowanie w pracy i wypełnianie obowiązków zawodowych. Materiał i metody. Badaniami objęto 145 osób, pracujących w szpitalach w Lublinie oraz Warszawie. Narzędziem badawczym był anonimowy kwestionariusz ankiety. Wyniki i wnioski. Stwierdzono, że średnio połowa badanego personelu medycznego jest zdania, że praca zawodowa, którą wykonują jest przyczyną bólu głowy. Wynika to z sytuacji stresowych mających związek ze specyfiką pracy oraz szkodliwych warunków pracy. Główna przyczyna bólu głowy wśród personelu medycznego to kontakt ze środkami do dezynfekcji powierzchni i skóry oraz kontakt z różnorodnymi środkami medycznymi i lekami. Słowa kluczowe: ból głowy, kadry medyczne szpitala, praca zawodowa. Abstract Introduction. Headache is a common condition that may result from an ongoing disease process in the body as well as be the result of negative health behaviors, improper lifestyle or harmful working conditions. Purpose. The aim of the work was the analysis of the frequency and the causes of headache among medical staff and its impact on the functioning of the working and professional duties. Material and methodology. The study group consisted of 145 people, chosen randomly, working in hospitals in Lublin and Warsaw. The study was based on questionnaire test. Results and conclusions. It was found that, on average, half of the medical staff is of the opinion that the work they perform is the cause of headache pain. This due to the stressful situations in connection with specificity of work and harmful working conditions. The main cause of headaches among medical personnel is contact with measures to surface and skin disinfectant and contact with a variety of medical measures and drugs. Key words: headache, medical staff, hospital; professional work.